Morning Yet On Judgement Day - Ekwuazi, Hyginus (Evans Brothers (Nigeria Publishers) Limited, 1987)
This book covers just a few hours in the life of four very articulate young Nigerians,all unemployed University Graduates.
Keywords: Play